DETERMINANTS AFFECTING THE SURVIVAL OF SMES IN MANADO - Christian, Yehezkiel; Massie, James D. D.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2019)
Abstract: Types of businesses keep on evolving and improving; the emergence of Small and Medium Enterprises (SMEs) proves as one of the solution for many entities to start a business with many kind of advantages. However the current status quo shows that lots of Small and Medium Enterprises failed to survive the competition which leads to the business to shut down their current operation. This research aims to analyze the determinants that affect the survival of SMEs in Manado, in this case are Human Capital, Vocational Skills, Entrepreneurial Skills and Research and Development. This study uses quantitative method with questionnaires used to collect the data, this research use Multiple Linear Regression as the tool of analysis. The samples in this research are 75 SMEs owners that already run the business for at least 6 months. The findings revealed that Human Capital and Research and Development have positive relationship but no significant influence toward the Survival of SMEs, while Vocational Skills and Entrepreneurial Skills have positive relationship and significant influence toward the Survival of SMEs. From the results, it is recommended to create a business incubator and entrepreneurial seminar in order to give better chance for SMEs to survive.Â Keywords: human capital, vocational skills, entrepreneurial skills, research and development, survival of SMEs